Optical quantum computers - Asavanant, Warit; Furusawa, Akira (New York: AIP Publishing, 2022)
"This book covers theoretical and experimental aspects of one of the most promising approaches to quantum computation: continuous-variable (CV) quantum computation using optical systems. In addition to its pedagogical values to the new entrants, the book is expected to also function as a basic handbook for both experimentalists and theorists working in the field. Moreover, this book will also summarize many recent experimental developments in the field. Although a few books that cover CV quantum information, with its rapid development, the currently available textbooks are starting to become obsolete. Also, a comprehensive textbook that covers both theoretical and experimental aspects of the field is still rare. This textbook will fill the void in the literature"--
Keywords: Quantum Computer